Integration of Digital Tools into Art Education (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The integration of digital technologies into art education holds significant importance in the modern education system. This article provides information on the advantages and limitations of using digital technologies in the field of art education. Additionally, it examines the main challenges encountered in this process and the ways to overcome them. Our goal is to assist teachers and students in further enhancing art education through the effective use of modern digital technologies.